Insurance related problems in bareboat charter agreements - Albano Gilabert Gascón (Journal of Shipping and Trade (JST), 2021)
In 2017, the majority of the United Kingdom Supreme Court held in its judgment in the Gard Marine and Energy v China National Chartering (The Ocean Victory) case that, in bareboat charters under the "BARECON 89" form, if both the owner and the charterer are jointly insured under a hull policy, the damages caused to the vessel by the charterer cannot be claimed by the insurer by way of subrogation after indemnifying the owner. The interpretation of the charter party leads to the conclusion that the liability between the parties is excluded. Faced with the Supreme Court's decision, the Baltic and International Maritime Council (BIMCO) adopted a new standard bareboat charter agreement only a few months later, the "BARECON 2017" form, which amends, among other clauses, the one related to insurance. The present paper analyses (i) the new wording of the clause mentioned above and (ii) its incidence on the relationship between the parties of both the charter agreement and the insurance contract and its consequences for possible third parties. Despite BIMCO's attempt to change the solution adopted by the Supreme Court and his willingness to allow the insurer to claim in subrogation against the person who causes the loss, the consequences, as it will be seen, do not differ much in practice when the wrongdoer is the co-insured charterer. On the contrary, when the loss is caused by a time charter or a sub-charter, in principle, there will be no impediment for the insurer to sue him.
Keywords: 650; Bareboat charter; BARECON; Joint and composite insurance; Marine insurance; Subrogation of the insurer